Choose me - Gerritsen, Tess; Braver, Gary (Seattle : Thomas & Mercer, 2021)
Taryn Moore is young, beautiful and brilliant, so why would she kill herself? When Detective Frankie Loomis arrives on the scene to investigate the girl's fatal plunge from her apartment balcony, she knows in her gut there's more to the story, especially after the autopsy reveals that the college senior was pregnant. It could be reason enough for suicide--or a motive for murder.
Keywords: Suicide -- Fiction; Women detectives -- Fiction; Murder -- Investigation -- Fiction; Secrecy -- Fiction; College teachers -- Fiction; College students -- Fiction; Psychological fiction; Detective and mystery fiction; Thrillers (Fiction)